32.4 A NOVEL TREATMENT FOR COGNITIVE IMPAIRMENT ASSOCIATED WITH SCHIZOPHRENIA BY ENHANCING THE ACTIVITY OF PARVALBUMIN INTERNEURONS. (9th April 2019) - Hutchison, John; Howes, Oliver; Marques, Tiago Reis; Kaar, Stephen; van den Berg, Frans; Large, Charles
Abstract: Background: Fast-spiking, parvalbumin-positive GABAergic interneurons in corticolimbic circuits modulate the synchronous firing of pyramidal neurons to enhance gamma-frequency oscillations which are thought to underpin cognitive function. Increasing evidence from post-mortem studies and animal models suggest that reduced activity of this class of interneuron may contribute to schizophrenia. Kv3 potassium channels are specifically expressed on PV interneurons and contribute to the rapid firing and transmitter release that is required to synchronize cortical networks. We have shown that positive modulation of Kv3 channels with a novel drug, AUT00206 can enhance the activity of PV interneurons and rescue cognitive function in animal models. Clinical evaluation of the potential of AUT00206 to treat schizophrenia includes assessment of the ability of the drug to modulate relevant neural circuitry and neurocognitive function, first in healthy volunteers (Phase 1a), and subsequently in patients (Phase 1b). Methods: The phase 1a clinical trial evaluated safety, tolerability and the pharmacokinetics of AUT00206 versus placebo in healthy male subjects aged between 18–45 years. Potential effect of the drug on cognitive performance was also evaluated using the Cambridge Neuropsychological Test Automated Battery (CANTAB) and potential effect on neural circuitry was assessed from measurement of auditory-evoked potentials, including the mismatch negativity (MMN) response. A phase 1b proof of clinical principal study is currently underway to establish whether AUT00206 administered for 28 days to patients within 5 years of a schizophrenia diagnosis can positively impact a relevant biomarker of the disease. Twenty-four patients (aged 18–50 years) with clinically and medically stable schizophrenia are being enrolled to receive either AUT00206 (16 subjects) or matching placebo (8 subjects). The primary objective is to assess the pharmacokinetics, safety and tolerability of the compound with secondary outcome assessing the effect of AUT00206 on MMN, with an exploratory endpoint of CANTAB at baseline and after drug treatment. Results: The phase 1a results support the cognitive safety of AUT00206 in healthy male volunteers across all cognitive domains known to be impaired in patients with schizophrenia and show preliminary evidence for a potential positive effect of AUT0020 800mg BID on sustained attention (CANTAB RVP; Rapid Visual Information Processing task). We also identified a possible effect of AUT00206 on reduction in latency of frequency deviant MMN. An interim blinded review of baseline data for the on-going phase 1b trial (N=14/24 schizophrenia patients) suggests a range of cognitive performance in patients at baseline, with MMN data at baseline in the phase 1b trial in line with expectation for patients with schizophrenia. Conclusions: Phase 1a study results support the cognitive safety, and potential efficacy, of AUT00206, a potent and selective modulator of Kv3.1 and Kv3.2 voltage-gated potassium channels in healthy volunteers using schizophrenia-relevant cognitive tests. The interim analysis of the phase 1b CANTAB data, an exploratory endpoint, in about 2/3 of the intended sample support previous findings that patients with schizophrenia are heterogeneous. In light of this finding, we will explore the data for correlations between baseline cognitive performance and treatment outcome.